Metabolism of cardiac glycosides studied in the isolated perfused guinea-pig liver - Kolenda, K.-D. (1971)
1. Metabolic degradation of tritiated ouabain, digoxin, and digitoxin has been investigated quantitatively using the isolated perfused guinea-pig liver. The cardiac glycosides and their metabolites have been extracted from the plasma, liver, and bile by different solvents and identified as far as possible by radio-chromatographic analysis. 2. The total metabolic activity in the experimental system was localized in the liver. 3. The hydrophilic glycoside ouabain could not penetrate into the metabolically active compartment of the liver and was, therefore, not degraded. The more lipophilic compound digitoxin, however, was completely degraded due to its high affinity for the metabolically active sites. The unchanged digitoxin cannot enter the aqueous bile fluid in contrast to its more hydrophilic metabolites. 4. The only detectable metabolic degradation of digoxin was a conjugation with glucuronic and/or sulphuric acid, but a cleavage of sugar molecules seemed not to occur. 5. In the case of digitoxin the metabolic processes are more complicated: sugar cleavage, conjugation, and C-12 hydroxylation take place simultaneously. An immediate hydroxylation of digitoxin leading to digoxin was not observed. After administration of digitoxin conjugation products as well as digoxigenin-bis-and digoxigenin-mono-digitoxosides were present in each of the compartments investigated, but the digitoxosides of digitoxigenin were intermediates in concentrations too low to be determined indicating a very high rate of conjugation and/or C-12 hydroxylation as compared with the cleavage of the digitoxoses. 6. A scheme for the metabolic pathways of the cardiac glycosides based on experimental results is presented. The metabolic behaviour of each of the three compounds involved is closely related to their physicochemical properties, especially the lipid solubility.